2013
DOI: 10.5194/nhess-13-2381-2013
|View full text |Cite
|
Sign up to set email alerts
|

On the puzzling feature of the silence of precursory electromagnetic emissions

Abstract: Abstract. It has been suggested that fracture-induced MHzkHz electromagnetic emissions (EME), which emerge from a few days up to a few hours before the main seismic shock occurrence permit a real-time monitoring of the damage process during the last stages of earthquake preparation, as it happens at the laboratory scale. Despite fairly abundant evidence, electromagnetic (EM) precursors have not been adequately accepted as credible physical phenomena. These negative views are enhanced by the fact that certain "… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 156 publications
2
17
2
Order By: Relevance
“…It is generally reported that there are considerable correlation between occurrence time of earthquakes and those of emission: the strength of electromagnetic emission increase before and/or after earthquake (e.g., [20,21] Fujinawa et al [46], Parrot et al [47]). Some reports suggest that MHz emission occur several weeks before and the VLF emission occurs only in the nucleation period [8,9,17] in contrary to the appearance of VLF type variation (C type) in this report. We do not have data to discuss the MHz event because of the detection frequency that is less than about 10 kHz.…”
Section: Radio Wave Emissioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It is generally reported that there are considerable correlation between occurrence time of earthquakes and those of emission: the strength of electromagnetic emission increase before and/or after earthquake (e.g., [20,21] Fujinawa et al [46], Parrot et al [47]). Some reports suggest that MHz emission occur several weeks before and the VLF emission occurs only in the nucleation period [8,9,17] in contrary to the appearance of VLF type variation (C type) in this report. We do not have data to discuss the MHz event because of the detection frequency that is less than about 10 kHz.…”
Section: Radio Wave Emissioncontrasting
confidence: 99%
“…Those evidences have been utilized to build the physical and statistical models of nucleation process [1,5]. These models have been further developed: for instance, superimposed undulation of foreshock activity was utilized to infer dynamical critical phenomena to estimate more exact final rupture time (e.g., Sornette and Sammis [7], Kapiris et al [8], Eftaxias et al [9], and many papers referred in the report).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a lot of evidence accumulated during the last few decades on the presence of electromagnetic phenomena associated with or prior to earthquakes (EQs), and such seismo-electromagnetic effects are considered to be promising for short-term EQ prediction (e.g., [1]- [3]). It is found that there are two different kinds of electromagnetic precursors: one is direct radiation in different frequency bands from the EQ hypocenter (or epicenter), and the other is seismo-atmospheric and -ionospheric perturbations (i.e., pre-EQ perturbations of the atmosphere and ionosphere) (e.g., [4]- [7]).…”
Section: Introductionmentioning
confidence: 99%